The Role of Government in the Implementation of Food Security Programs through Catfish Farming (lele) - Amat Antoni; Wargo; Zaenal Abidin (Zabags Qu Publish, 2025)
This study examines the role of local government in implementing a food security program based on catfish (lele) farming in Kelurahan Talang Babat, focusing on four dimensions: public policy and institutional support, communication and outreach, human resource development, and financing and infrastructure management. Adopting a qualitative phenomenological approach, the research draws on in-depth interviews with farmers and government actors, direct field observation, and documentary evidence; data were analyzed thematically with triangulation across sources. Findings indicate that while local authorities have facilitated group formation, provided initial inputs, and conducted introductory outreach, program effectiveness is constrained by one-way communication, limited farmer capacity to operate modern bioflok technology, inadequate follow-up financing, and inconsistent monitoring. These constraints reduce the program’s ability to achieve sustained production gains and community resilience. The study contributes theoretically by situating public policy and governance variables within a micro-level aquaculture context and practically by recommending continuous technical extension, group-based financing models, and participatory monitoring mechanisms to enhance the sustainability and self-reliance of community-based food security initiatives.